Changes and Development in Marketing and Strategies - Study on ASUS Computer Inc. - Rudresh Pandey; Liem Gai Sin; Shreyas Agnihotri; Utkarsh Chaudhary; Natasha Tiffany; Ahmad Usamah; Daisy Mui Hung Kee; Hafiz Zikri; Muhammad Hafizudin; Mohamad Zulfaqar (AIBPM Publisher, 2021)
Computers have highly evolved and a lot of companies, such ASUS, have consistently improving and innovating computers and other products. ASUS stands as the world’s 6th largest PC Vendor in 2020, mission of which is to deliver innovative and spectacular IT solutions. This research investigates how ASUS developed into a tech giant and what techniques and strategies they used to capture such great market share. The research will also contain certain additional ideas that Asus can work upon to be the no. 1 Tech giant in the world and the USP (Unique Selling Proposition) of Asus product line of and the advantages and disadvantages over competitors. Furthermore, comparison of Asus’s major rivals will give a better understanding of their decisions taken in the last 10 years.